The Tonkin weakfish, Cynoscion similis (Sciaenidae, Perciformes), an endemic species of the Amazonas-Orinoco Plume - Caires, Rodrigo Antunes; Santos, Wagner C. R. dos; Machado, Leonardo; Oliveira, Claudio [UNESP]; Cerqueira, Najila N. C. D. [UNESP]; Rotundo, Matheus Marcos; Oliveira, Cintia; Marceniuk, Alexandre P. (Inst Nacional Pesquisas Amazonia, 2019)
Despite its importance in biogeographical, ecological, and commercial terms, the fish fauna of the northern Brazilian coast is still poorly known, representing the least sampled portion of the Brazilian Exclusive Economic Zone. We collected Tonkin weakfish, Cynoscion similis specimens during extensive surveys of the northern Brazilian coast and concluded that C. similis is common in this region. While the species had not previously been reported for the northern Brazilian state of Para, it may have been recorded in studies of industrial fisheries, being identified only as Cynoscion sp. or by the common name pescada negra. This reinforces the need for the reliable taxonomical identification of species, to guarantee the collection of accurate data on ecology and fisheries, and ultimately, support the development of effective conservation strategies. Here we provide additional morphological and molecular data to distinguish Cynoscion similis from the closely related Cynoscion jamaicensis, and other congeners.
Keywords: Brazilian north coast; Cynoscion jamaicensis; industrial fisheries; DNA barcoding; reliable taxonomical identification